A Study of Prevalence of Extended-spectrum B Lactamase Producing Enterobacteriaceae from Urinary Isolates in Community Setting. Issue 2 (2013) - lohidakshan, Syeda Nusheen Fathima. Lolith; Samson, Manju
No abstract available